Polyolefin-based resin film
Patent Information
- Application Number
- JP2024195075
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-03-25
AI Technical Summary
【0017】 本発明のポリオレフィン系樹脂フィルムは、直進カット性、引裂きやすさ、製袋加工性に優れ、レトルト後も落下時に破袋しにくく、かつ開封時にヒゲが発生しにくい。特にレトルトパウチに適している。
Smart Images

Figure 2025026894000001 
Figure 2025026894000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyolefin resin film and at least one base film selected from the group consisting of a polyamide resin film, a polyester resin film, and a polypropylene resin film. [Background technology]
[0002] Packaging bags are typically produced by heat sealing the peripheral portions of a laminate of a base film, such as a polyamide resin film, polyester resin film, or polypropylene resin film, and a polyolefin resin film, with the polyolefin resin film surfaces in contact with each other at a temperature close to the melting point of the polyolefin resin film. In food packaging bags, so-called retort pouches are widely used, which are filled with food and then sterilized with pressurized steam at about 130°C, making them suitable for storing food for long periods of time. In recent years, the demand for retort pouches has increased due to social factors such as the advancement of women into the workforce, the trend toward nuclear families, and the aging of the population, and at the same time, there is a demand for further improvement in their properties. For example, in recent years, these retort pouches are often packed in boxes, transported, and sold in stores, so they are required to be resistant to breakage even if dropped during this process, particularly when dropped under refrigeration.
[0003] Furthermore, when removing food contents from a packaging bag, particularly a retort pouch, the packaging bag is often torn by hand from a cut portion, known as a notch portion, made in the heat-sealed portion around the periphery of the packaging bag; however, when a conventional laminate is used, the packaging bag cannot be torn parallel to one side, which is usually the horizontal direction, and is instead opened at an angle, or the tear direction of the laminate on the front and back sides of the packaging bag is reversed on the top and bottom, known as tear-splitting, occurs, making it difficult to remove the food contents and causing the food contents to stain hands or clothes, or causing burns if the contents are heated.
[0004] The reason why it is difficult to tear a packaging bag parallel to one side of the packaging bag is that the base film used in the laminate is distorted, i.e., the molecular orientation axis direction of the base film is not parallel to one side of the package.
[0005] If the molecular orientation axis direction of the base film can be made the same as the tear direction of the packaging bag, such a problem will not occur. The molecular orientation axis direction of the produced wide-width stretched film in the width direction center part coincides with the running direction of the film, and it is possible to tear it parallel to one side of the packaging bag. However, the molecular orientation axis direction at the width direction end of the base film is inclined from the running direction of the film, and even if the running direction of the film is processed to coincide with the vertical or horizontal direction of the packaging bag, the tear direction of the packaging bag will be inclined to the molecular orientation axis direction of the base film. It is not practical to procure the base film using the width direction end of the film completely, and the degree of distortion tends to be even greater than before as the production speed of the base film increases and the width of the base film increases. Therefore, attempts have been made to solve these problems by improving the polyolefin resin film that is laminated to the base film.
[0006] A film obtained by uniaxially stretching a polyolefin resin sheet containing an ethylene-propylene block copolymer and an ethylene-propylene copolymer at a stretch ratio of 3.0 or less is known from Patent Document 1. However, there is room for improvement in tear strength, and there is a problem that tearing easily occurs.
[0007] In addition, Patent Documents 2 and 3 disclose a film obtained by uniaxially stretching a polyolefin resin sheet containing a propylene-ethylene block copolymer or a propylene-ethylene random copolymer, and a propylene-butene elastomer and / or an ethylene-butene elastomer at about 5 times its original length. However, this has the problem that the dimensional stability against heat is poor, and the heat applied during retort treatment causes the package to deform and impair its appearance, and the package is easily broken at low temperatures. Also, a film is known from Patent Document 4, which is obtained by uniaxially stretching a polyolefin resin sheet mainly composed of a propylene-ethylene block copolymer at about four times its original size. However, when a four-side sealed bag made from a laminate with a biaxially stretched polyamide film or the like is torn open from a notch, there is a problem that thread-like pieces of film separate from the heat seal edge (commonly known as whiskers). [Prior art documents] [Patent documents]
[0008] Patent Document 1: Patent No. 5790497 Patent Document 2: JP 2014-141302 A Patent Document 3: Special Publication No. 2012-500307 Patent document 4: WO2019 / 123944A1 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to provide a polyolefin-based resin film which, even when laminated with a base film having a large distortion in the molecular orientation axis such as a biaxially oriented polyamide-based resin film, provides a packaging bag obtained from the laminate which has excellent straight-line cuttability, tearability and bag-making processability, is unlikely to break when dropped after retorting, and is unlikely to produce whiskers when opened. [Means for solving the problem]
[0010] As a result of intensive research into achieving this object, the present inventors have found that a polypropylene-based resin film can be obtained that is composed of a polypropylene-based resin composition containing, in addition to a propylene-ethylene block copolymer and a propylene-α-olefin random copolymer, an ethylene-propylene copolymer elastomer and a propylene-butene copolymer elastomer, and that while the polymer molecules are mainly oriented in one direction by stretching, the heat shrinkage rate in each direction is reduced and the orientation of the molecular chains in the longitudinal direction is within a specific range, so that even when laminated with a base film such as a biaxially stretched polyamide-based resin film that has a large distortion in the molecular orientation axis, a packaging bag obtained from the laminate has excellent straight-line cuttability, tearability and bag-making processability, is not easily broken when dropped even after retorting, and is not easily frayed when opened, thereby completing the present invention. That is, the present invention has the following aspects.
[0011] [1] A polyolefin-based resin film made of a polypropylene-based resin composition, comprising, in a total of 100 parts by weight of polypropylene-based resin, 40 to 97 parts by weight of a propylene-ethylene block copolymer, 0 to 50 parts by weight of a propylene-α-olefin random copolymer or a propylene homopolymer, and 3 to 10 parts by weight of at least one elastomer selected from the group consisting of an ethylene-propylene copolymer elastomer, a propylene-butene copolymer elastomer, and an ethylene-butene copolymer elastomer, wherein the polyolefin-based resin film has a thermal shrinkage rate in the longitudinal direction of 1% or more and 9% or less, and an x-axis orientation coefficient ΔNx calculated from the refractive index of 0.0150 or more and 0.0250 or less.
[0012] [2] The polyolefin resin film according to [1], which has a multi-layer structure of at least two layers.
[0013] [3] A laminate with at least one base film selected from the group consisting of the polyolefin resin film according to [1] or [2], a polyamide resin film, a polyester resin film, and a polypropylene resin film.
[0014] [4] The laminate according to [3], having a straight cut ability of 5 mm or less.
[0015] [5] A packaging body comprising the laminate described in [4].
[0016] [6] The packaging body described in [5], which is for retort use. Effect of the Invention
[0017] The polyolefin resin film of the present invention has excellent straight cuttability, tearability, and processability for making bags, is resistant to tearing when dropped after retorting, and is resistant to creases when opened. It is particularly suitable for retort pouches. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below. (Propylene-ethylene block copolymer) In the present invention, a propylene-ethylene block copolymer can be used. The propylene-ethylene block copolymer in the present invention is a multi-stage copolymer consisting of a first polymerization step of a copolymerization component of a large amount of propylene and a small amount of ethylene, and a second polymerization step of a copolymerization component of a small amount of propylene and a large amount of ethylene. Specifically, as shown in JP-A-2000-186159, it is preferable to use one that has been subjected to gas phase polymerization. That is, a block copolymer obtained by polymerizing a polymer portion (component A) mainly composed of propylene in the substantial absence of an inert solvent in the first step, and then polymerizing a copolymer portion (component B) of propylene and ethylene having an ethylene content of 20 to 50 parts by weight in the gas phase in the second step can be mentioned, but is not limited thereto.
[0019] The melt flow rate (MFR) of the propylene-ethylene block copolymer (measured at 230°C under a load of 2.16 kg) is preferably 1 to 10 g / 10 min, more preferably 2 to 7 g / 10 min. If it is 1 g / 10 min or more, it is easy to extrude it through a T-die, and conversely, if it is 10 g / 10 min or less, it is easy to increase the impact strength (impact strength).
[0020] In the present invention, the xylene soluble portion at 20°C is called CXS, and the xylene insoluble portion at 20°C is called CXIS. In the propylene-ethylene block copolymer used in the present invention, CXS is mainly composed of a rubber component (component B), and CXIS is mainly composed of a polypropylene component (component A). When the intrinsic viscosities of each are [η]CXS and [η]CXIS, the value of [η]CXS and [η]CXIS is preferably in the range of 1.8 to 3.8 dl / g, and more preferably in the range of 2.0 to 3.0 dl / g. When it is 3.0 dl / g or less, fish eyes are unlikely to occur in the polyolefin resin film. On the other hand, when it is 1.8 dl / g or more, the heat seal strength between polyolefin resin films is unlikely to be significantly reduced. On the other hand, [η]CXIS is preferably in the range of 1.0 to 3.0 dl / g. When it is 3.0 dl / g or less, extrusion through a T-die is easy, and conversely, when it is 1.0 dl / g or more, it is easy to increase the impact strength (impact strength) of the film.
[0021] The above [η]CXS and [η]CXIS are values measured by the following measurement method. 5 g of sample was completely dissolved in 500 ml of boiling xylene, cooled to 20°C, and left for 4 hours or more. Next, this was separated into a filtrate and a precipitate by filtration, and the intrinsic viscosity ([η]) of the component (CXS) obtained by drying the filtrate and the solid (CXIS) obtained by drying the precipitate under reduced pressure at 70°C was measured in tetralin at 135°C using an Ubbelohde viscometer.
[0022] It is generally known that there is a correlation between MFR and the intrinsic viscosity η of the entire film. By knowing the η of the film, it is possible to roughly determine the MFR of the resin used. η is a guide to molecular weight, with a larger value indicating a larger molecular weight and a smaller value indicating a smaller molecular weight. MFR is a guide to molecular weight, with a smaller value indicating a larger molecular weight and a larger value indicating a smaller molecular weight.
[0023] In addition, the copolymerization ratio of the ethylene component in the propylene-ethylene block copolymer is preferably 1 to 15% by weight, more preferably 3 to 10% by weight, and more preferably 85 to 99% by weight, more preferably 90 to 97% by weight.
[0024] The lower limit of the melting point of the propylene-ethylene block copolymer is not particularly limited, but is preferably 120°C, more preferably 125°C. At 120°C or higher, heat resistance is easily obtained, and the inner surfaces of the bag are less likely to fuse together during retort treatment. The upper limit of the melting point of the propylene-ethylene block copolymer is not particularly limited, but is preferably 175°C, more preferably 170°C. If it is 175°C or lower, the heat sealing temperature is likely to decrease.
[0025] Specific examples of propylene-ethylene block copolymers include a block copolymer polypropylene resin having an ethylene content of 7% by weight and a CXS intrinsic viscosity η=3.0 dl / g (MFR=3.0 g / 10 min at 230° C. and a load of 2.16 kg, melting point: 164° C., WFS5293-22 manufactured by Sumitomo Chemical Co., Ltd.) and a block copolymer polypropylene resin having an ethylene content of 6% by weight and a CXS intrinsic viscosity η=2.3 dl / g (MFR=3.0 g / 10 min at 230° C. and a load of 2.16 kg, melting point: 164° C., WFS5293-29 manufactured by Sumitomo Chemical Co., Ltd.).
[0026] (Propylene-α-olefin random copolymer) In the present invention, it is preferable to add a propylene-α-olefin random copolymer for the purpose of lowering the heat sealing temperature of the polyolefin resin film. The propylene-α-olefin random copolymer may be a copolymer of propylene and at least one α-olefin having 2 to 20 carbon atoms other than propylene. Examples of the α-olefin monomer having 2 to 20 carbon atoms include ethylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, and octene-1. Although not particularly limited, it is preferable to use ethylene in terms of compatibility with propylene-ethylene block copolymers. If necessary, two or more kinds of propylene-α-olefin random copolymers can be mixed and used. Propylene-ethylene random copolymers are particularly suitable. In this report, the monomers constituting the random copolymers are named and described in order of their composition ratio.
[0027] The lower limit of the melt flow rate (MFR) of the propylene-α-olefin random copolymer at 230° C. and a load of 2.16 kg is preferably 0.6 g / 10 min, more preferably 1.0 g / 10 min, and even more preferably 1.2 g / 10 min. If it is 0.6 g / 10 min or more, the compatibility with the propylene-ethylene block copolymer increases and the film is less likely to whiten. The upper limit of the melt flow rate of the propylene-α-olefin random copolymer is preferably 10.0 g / 10 min, more preferably 8.0 g / 10 min, and even more preferably 7.0 g / 10 min.
[0028] It is preferable to use a propylene-α-olefin random copolymer containing a metallocene-based olefin polymerization catalyst as the polymerization catalyst used for producing the propylene-α-olefin random copolymer. The propylene-α-olefin random copolymer containing a metallocene-based olefin polymerization catalyst is characterized by having a low content of components in the low molecular weight region and the high molecular weight region. It has also been newly discovered that the use of a propylene-α-olefin random copolymer containing a metallocene-based olefin polymerization catalyst suppresses the occurrence of whiskers. The metallocene olefin polymerization catalyst is a catalyst comprising (i) a transition metal compound of Group 4 of the periodic table containing a ligand having a cyclopentadienyl skeleton (a so-called metallocene compound), (ii) a co-catalyst capable of reacting with the metallocene compound to activate it to a stable ionic state, and, if necessary, (iii) an organoaluminum compound, and any of the known catalysts can be used.
[0029] The copolymerization ratio of the ethylene component in the propylene-α-olefin random copolymer is preferably 1 to 15% by weight, more preferably 3 to 10% by weight, and the copolymerization ratio of the propylene component in the propylene-ethylene block copolymer is preferably 85 to 99% by weight, more preferably 90 to 97% by weight.
[0030] The lower limit of the melting point of the propylene-α-olefin random copolymer is preferably 120° C., more preferably 125° C. At temperatures above 120° C., heat resistance is easily obtained, and the inner surfaces of the bag may fuse together during retort treatment. The upper limit of the melting point of the propylene-α-olefin random copolymer is preferably 145° C., more preferably 140° C. If it is 145° C. or lower, the heat sealing temperature tends to decrease.
[0031] Specific examples of propylene-α-olefin random copolymers include S131 manufactured by Sumitomo Chemical Co., Ltd. (ethylene content: 5.5% by weight, density: 890 kg / m3, MFR at 230°C and a load of 2.16 kg: 1.5 g / 10 m8 in, melting point: 132°C, Ziegler-Natta catalyst), propylene-ethylene random copolymer WFW4M manufactured by Japan Polypropylene Co., Ltd. (ethylene content: 7% by weight, density: 900 kg / m3, MFR at 230°C and a load of 2.16 kg: 7.0 g / 10 min, melting point: 136°C, metallocene catalyst), and WFX4M manufactured by Japan Polypropylene Co., Ltd. (ethylene content: 7% by weight, density; 900 kg / m3, 230°C, MFR at 230°C and a load of 2.16 kg: 7.0 g / 10 min, melting point: 125°C, metallocene catalyst).
[0032] (Propylene homopolymer) In the present invention, a propylene homopolymer can be used. Examples of the propylene homopolymer include isotactic polypropylene, which has high crystallinity and excellent rigidity and heat resistance, and atactic polypropylene, which has low crystallinity and excellent flexibility. The propylene homopolymer to be used is preferably isotactic polypropylene, which has high crystallinity and is capable of suppressing deterioration of the heat shrinkage rate. The melt flow rate (MFR) of the propylene homopolymer (measured at 230°C under a load of 2.16 kg) is preferably 1 to 10 g / 10 min, and more preferably 2 to 7. If it is 1 g / 10 min or more, extrusion through a T-die is easy, and conversely, if it is 10 g / 10 min or less, the impact strength (impact strength) of the film is easily increased.
[0033] Propylene homopolymers containing metallocene-based olefin polymerization catalysts are characterized by a narrower molecular weight distribution and fewer components on the lower and higher molecular weight sides than the weight average molecular weight index, compared to propylene homopolymers containing Ziegler-Natta-based olefin polymerization catalysts. It has also been newly discovered that the generation of whiskers is suppressed when propylene homopolymers containing metallocene-based olefin polymerization catalysts are used. Furthermore, they have excellent flexibility and strength. A metallocene-based olefin polymerization catalyst is a catalyst consisting of (i) a transition metal compound of Group 4 of the periodic table containing a ligand having a cyclopentadienyl skeleton (a so-called metallocene compound), (ii) a cocatalyst that can be activated to a stable ion state by reacting with the metallocene compound, and, if necessary, (iii) an organoaluminum compound, and any known catalyst can be used.
[0034] Specific examples of propylene homopolymers include F300SP manufactured by Prime Polymer Co., Ltd. (ethylene content: 0 wt%, density: 890 kg / m3, MFR: 3.0 g / 10 min at 230°C and a load of 2.16 kg, melting point: 160°C, Ziegler-Natta catalyst).
[0035] (copolymer elastomer) In the present invention, a copolymer elastomer is used as a constituent component of the polyolefin resin film of the present invention for the purpose of improving the drop-breakage resistance of the packaging bag of the present invention. Examples of copolymer elastomers include olefin-based thermoplastic elastomers, such as olefin-based thermoplastic copolymers that exhibit rubber-like elasticity around room temperature, and / or olefin-based thermoplastic copolymer elastomers that exhibit relatively high Shore hardness and good transparency. As such a copolymer elastomer, at least one elastomer selected from the group consisting of ethylene-propylene copolymer elastomer, propylene-butene copolymer elastomer, and ethylene-butene copolymer elastomer may be used, with ethylene-propylene copolymer elastomer being preferred from the viewpoint of impact resistance and heat seal strength. The ethylene-propylene copolymer elastomer refers to a non-crystalline or low-crystalline elastomer obtained by copolymerizing ethylene and propylene among thermoplastic elastomers.
[0036] The copolymer elastomer used in the present invention preferably has a melt flow rate (MFR) of 0.2 to 5 g / 10 min at 230°C and a load of 2.16 kg, a density of 820 to 930 kg / m3, and a molecular weight distribution (Mw / Mn) of 1.3 to 6.0 as determined by the GPC method. When the copolymer elastomer in the present invention has a melt flow rate (MFR) of 0.2 g / 10 min or more at 230° C. under a load of 2.16 kg, it is easy to knead uniformly and fish eyes are less likely to occur, and when it is 5 g / min or less, bag rupture resistance is easily improved. The intrinsic viscosity [η] of the copolymer elastomer in the present invention is preferably 1.0 to 5.0, more preferably 1.2 to 3.0, from the viewpoints of heat seal strength retention, impact strength retention, and bag drop strength. When the intrinsic viscosity [η] is 1.0 or more, uniform kneading is easy and fish eyes are unlikely to occur, and when it is 5.0 or less, bag breakage resistance and heat seal strength are likely to be improved.
[0037] The copolymerization ratio of the ethylene component in the ethylene-propylene copolymer elastomer, the propylene-butene copolymer elastomer, and the ethylene-propylene copolymer elastomer is preferably 55 to 85% by weight, and more preferably 60 to 80% by weight.The copolymerization ratio of the propylene component in the ethylene-propylene copolymer elastomer is preferably 15 to 45% by weight, and more preferably 20 to 40% by weight.
[0038] Specific examples of the ethylene-propylene copolymer elastomer in the present invention include an ethylene-propylene copolymer elastomer having a propylene content of 27% by weight, a density of 870 kg / m3, and an MFR (230°C, 2.16 kg) of 1.8 g / 10 min (Tafmer P0480 manufactured by Mitsui Chemicals, Inc.).
[0039] (Polyolefin resin film) The polyolefin resin film of the present invention may be a single layer or may be composed of two or more layers. For example, it may have a three-layer structure of a heat seal layer / laminate layer or a heat seal layer / intermediate layer / laminate layer, and each layer may be composed of multiple layers.
[0040] The heat seal layer is a layer located on the outermost surface side of a polyolefin resin film, and a package can be produced by facing the surfaces of the layers together and subjecting them to thermocompression bonding. The layer located on the outermost surface side opposite to the heat seal layer is a laminate layer, which can be laminated by bonding with a base film such as a polyester film or a polyamide film. In the case of a three-layer structure of heat seal layer / intermediate layer / laminate layer, the ends of the film product of the present invention or the film itself can be recovered and re-pelletized to use as the raw material for the intermediate layer, thereby reducing the cost of the film product without impairing properties such as straight cuttability, ease of tearing, bag-making processability, and bag-breaking resistance.
[0041] In each layer of the polyolefin resin film of the present invention, the balance of properties such as tearability, heat seal strength, and bag rupture resistance can be adjusted by changing the mixing ratio of at least one elastomer selected from the group consisting of propylene-ethylene block copolymer, propylene-α-olefin random copolymer or propylene homopolymer, ethylene-propylene copolymer elastomer, propylene-butene copolymer elastomer, and ethylene-butene copolymer elastomer in each layer.
[0042] (Propylene-ethylene block copolymer) In each layer of the polyolefin resin film of the present invention, the content of the propylene-ethylene block copolymer in a total of 100 parts by weight of the polypropylene resin is in the range of 40 to 97 parts by weight, preferably 60 parts by weight or more, and more preferably 85 parts by weight or less, from the viewpoint of separation. When the ratio of the propylene-ethylene block copolymer is 40 parts by weight or more, the shrinkage rate tends to be small and the resistance to bag breakage tends to be improved.When the ratio is 97 parts by weight or less, the heat sealability at low temperatures tends to be obtained.
[0043] (Propylene-α-olefin random copolymer or propylene homopolymer) In each layer of the polyolefin resin film of the present invention, the content of propylene-α-olefin random copolymer or propylene homopolymer in a total of 100 parts by weight of polypropylene resin is in the range of 0 to 50 parts by weight from the viewpoint of separation, preferably 5 parts by weight or more and 40 parts by weight or less, and more preferably 15 parts by weight or more. When the content of propylene-α-olefin random copolymer or propylene homopolymer is 5 parts by weight or more, it is easy to obtain heat sealability at low temperatures and the heat seal strength is easy to increase, and when it is 50 parts by weight or less, it is easy to reduce the heat shrinkage rate.
[0044] (copolymer elastomer) In each layer of the polyolefin resin film of the present invention, the content of at least one elastomer selected from the group consisting of ethylene-propylene copolymer elastomer, propylene-butene copolymer elastomer, and ethylene-butene copolymer elastomer is in the range of 3 parts by weight or more and 10 parts by weight or less, and the content of the ethylene-propylene copolymer elastomer is preferably in the range of 4 to 9 parts by weight, and more preferably in the range of 5 to 8 parts by weight, per 100 parts by weight of the polypropylene resin in total. By containing 3 parts by weight or more of at least one elastomer selected from the group consisting of ethylene-propylene copolymer elastomer, propylene-butene copolymer elastomer, and ethylene-butene copolymer elastomer, heat sealability and bag rupture resistance are easily obtained when ease of tearing is imparted, and by containing 10 parts by weight or less, the appearance (transparency) of the film is improved.
[0045] The polyolefin resin film of the present invention has a sea-island structure consisting of a matrix polymer and domains, and thus exhibits good resistance to rupture of the bag. The matrix polymer is mainly composed of a propylene-based portion of a propylene-ethylene block copolymer and a propylene-α-olefin random copolymer, and the domains are mainly composed of an ethylene-propylene copolymer elastomer and a portion of a propylene-ethylene block copolymer each consisting of ethylene.
[0046] (Additives) The polypropylene resin composition of the present invention may contain an antiblocking agent. The antiblocking agent to be blended is not particularly limited, but may be inorganic particles such as calcium carbonate, silicon dioxide, titanium dioxide, barium sulfate, magnesium oxide, talc, zeolite, etc., acrylic, styrene, styrene-butadiene polymers, or organic particles made of crosslinked bodies thereof. Considering the ease of controlling the particle size distribution, dispersibility, ease of maintaining the optical appearance, and prevention of particles from falling off the film, organic particles made of crosslinked bodies are preferred. As the crosslinked body, crosslinked acrylic polymers made of acrylic monomers such as acrylic acid, methacrylic acid, acrylic acid esters, methacrylic acid esters, etc. are particularly preferred, and crosslinked polymethyl methacrylate is more preferred. The surfaces of these particles may be coated with various coatings for the purposes of improving dispersibility and preventing them from falling off. The shape of these particles may be amorphous, spherical, elliptical, rod-like, angular, polyhedral, conical, or even porous having cavities on the particle surface or inside. The antiblocking agent preferably has an average particle size of 3 to 12 μm in terms of the appearance and blocking resistance of the film. Although using only one type of anti-blocking agent is effective, blending two or more types of inorganic particles with different particle sizes and shapes can result in more complex protrusions being formed on the film surface, resulting in a more advanced anti-blocking effect. When a block copolymer is used as the main constituent resin, the dispersion of the polymer may result in the formation of surface irregularities, and a high level of anti-blocking effect may be obtained even without the addition of an anti-blocking agent.
[0047] The polypropylene resin composition of the present invention may contain an organic lubricant. The lubrication and anti-blocking effect of the laminated film are improved, and the film is easy to handle. The reason for this is believed to be that the organic lubricant bleeds out and is present on the film surface, thereby exerting a lubricant effect and a mold release effect. Furthermore, it is preferable to add an organic lubricant having a melting point above room temperature. Examples of suitable organic lubricants include fatty acid amides and fatty acid esters. More specifically, oleic acid amide, erucic acid amide, behenic acid amide, ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, ethylene bisoleic acid amide, and the like. These may be used alone, but it is preferable to use two or more of them in combination, as this may allow the lubrication and anti-blocking effect to be maintained even under harsher environments.
[0048] The polypropylene resin composition of the present invention may contain, as necessary, appropriate amounts of antioxidants, antistatic agents, antifogging agents, neutralizing agents, nucleating agents, colorants, other additives, inorganic fillers, etc., within the scope of the object of the present invention. Examples of antioxidants include phenolic and phosphite antioxidants used alone or in combination, or antioxidants having both phenolic and phosphite skeletons in one molecule used alone.
[0049] (Method of manufacturing polyolefin resin film) The polyolefin resin film of the present invention can be formed by, for example, inflation method or T-die method, but the T-die method is preferred for increasing transparency and ease of drafting. The inflation method uses air as a cooling medium, whereas the T-die method uses a cooling roll, making it an advantageous manufacturing method for increasing the cooling rate of the unstretched sheet. By increasing the cooling rate, the crystallization of the unstretched sheet can be suppressed, resulting in high transparency, and it is advantageous in that the load applied to the stretching in the subsequent process can be easily controlled. For these reasons, it is more preferable to form the film by the T-die method.
[0050] The lower limit of the cooling roll temperature when the molten raw resin is cast to obtain a non-oriented sheet is preferably 15°C, more preferably 20°C. If it is less than the above, condensation occurs on the cooling roll, causing insufficient adhesion between the unstretched sheet and the cooling roll, which may cause thickness defects. The upper limit of the cooling roll is preferably 50°C, more preferably 40°C. If it is 50°C or less, the transparency of the polyolefin resin film is less likely to deteriorate.
[0051] Methods for stretching a non-oriented sheet include, for example, an inflation method, a tenter transverse stretching method, and a roll longitudinal stretching method, but the roll longitudinal stretching method is preferred because of ease of control of orientation. By stretching a non-oriented sheet under appropriate conditions, the sheet exhibits straight cut properties because the molecular chains are regularly aligned in the stretching direction. The lower limit of the stretching ratio is preferably 2.8 times, more preferably 3.3 times. If it is 2.8 times or more, the tear strength in the stretching direction is unlikely to increase, and straight cuttability is easily obtained. It is more preferably 3.4 times, and even more preferably 3.5 times. The upper limit of the stretching ratio is preferably 3.9 times. If it is 3.9 times or less, excessive orientation is unlikely to proceed and the thermal shrinkage rate in the longitudinal direction is unlikely to increase. The upper limit of the stretching ratio is more preferably 3.8 times.
[0052] The lower limit of the stretching roll temperature is preferably 80° C. If the temperature is 80° C. or higher, the stretching stress applied to the film does not become too high, and the shrinkage rate is unlikely to become large. The upper limit of the stretching roll temperature is preferably 140° C. If the temperature is 140° C. or lower, the stretching stress applied to the film is not too low, and the thermal shrinkage rate of the film in the longitudinal direction is not too low, and the film is not easily fused to the stretching roll. The upper limit of the stretching roll temperature is more preferably 130° C., even more preferably 125° C., and particularly preferably 115° C.
[0053] It is preferable to bring the unstretched sheet into contact with a preheat roll to increase the sheet temperature before it is introduced into the stretching step. The lower limit of the preheat roll temperature when stretching a non-oriented sheet is preferably 80° C., more preferably 90° C. If it is 80° C. or higher, the stretching stress does not become too high, and thickness fluctuation is unlikely to worsen. The upper limit of the preheat roll temperature is preferably 140° C., more preferably 130° C., and even more preferably 125° C. If it is 140° C. or lower, the film is unlikely to stick to the roll, and film thickness fluctuation is unlikely to increase.
[0054] The polyolefin resin film that has been stretched is preferably annealed to suppress thermal shrinkage. Annealing methods include roll heating and tentering, but roll heating is preferred because of the simplicity of the equipment and ease of maintenance. Annealing reduces the internal stress of the film, thereby suppressing thermal shrinkage in the longitudinal direction of the film, and therefore does not sacrifice the longitudinal heat shrinkage rate or heat seal strength compared to the conventional method of simply increasing the stretch ratio to increase tearability. However, this may have a negative effect on properties other than the longitudinal heat shrinkage rate and heat seal strength, but the present invention can suppress the negative effect on bag breakage resistance by using a copolymer elastomer in combination.
[0055] The lower limit of the annealing temperature is preferably 100° C. If the temperature is below 100° C., the thermal shrinkage rate in the longitudinal direction is unlikely to increase, the tear strength is unlikely to increase, and the finish of the packaging bag after bag making or retorting may deteriorate. It is more preferably 115° C., and particularly preferably 125° C. The upper limit of the annealing temperature is preferably 140° C. The higher the annealing temperature, the more likely it is that the thermal shrinkage in the longitudinal direction will decrease, but if the annealing temperature exceeds this limit, the film thickness fluctuation may worsen or the film may melt and adhere to the production equipment. The upper limit of the annealing temperature is more preferably 135° C.
[0056] In the annealing step, a relaxation step can be provided by gradually slowing down the film transport speed, for example by slowing down the rotation speed of the roll after heating. By providing the relaxation step, the thermal shrinkage rate of the produced polyolefin resin film can be reduced. The upper limit of the relaxation rate in the relaxation step is preferably 10%, more preferably 8%. If it is 10% or less, the heat shrinkage rate is not too small. The lower limit of the relaxation rate is preferably 1%, more preferably 3%. If it is 1% or more, the heat shrinkage rate in the longitudinal direction of the polyolefin resin film is unlikely to become high.
[0057] In the present invention, it is preferable to activate the surface of the polyolefin resin film to be laminated by corona treatment or the like. This improves the lamination strength with the base film. The laminate surface is provided on the opposite side to the heat seal surface.
[0058] (Properties of polyolefin resin film) (film thickness) The lower limit of the thickness of the polyolefin resin film of the present invention is preferably 10 μm, more preferably 30 μm. If it is less than the above, it will be relatively thin compared to the thickness of the base film, so that the straight cut property as a laminate may be deteriorated, and the stiffness of the film may be too weak to be processed, and the impact resistance may be reduced, and the bag break resistance may be deteriorated. The upper limit of the film thickness is preferably 200 μm, more preferably 130 μm. If it exceeds the above, the stiffness of the film may be too strong to be processed, and it may be difficult to produce a suitable package.
[0059] (Longitudinal orientation factor) The longitudinal orientation coefficient ΔNx used in the present invention can be calculated by Equation 1. ΔNx=Nx-(Ny+Nz) / 2 (Equation 1) Nx: Refractive index in the longitudinal direction Ny: Refractive index in the longitudinal direction and perpendicular direction to the thickness direction Nz: Refractive index in the thickness direction The lower limit of the longitudinal orientation coefficient ΔNx of the polyolefin resin film of the present invention is 0.0150, more preferably 0.0180, and even more preferably 0.0200. If it is 0.0150 or more, the straight cuttability of the package is easily obtained. The upper limit of the longitudinal orientation coefficient ΔNx is preferably 0.0250, more preferably 0.0245, even more preferably 0.0240, even more preferably 0.0230, and particularly preferably 0.0220. If it is 0.0250 or less, the heat seal strength is not likely to decrease.
[0060] (Heat shrinkage rate) The upper limit of the heat shrinkage rate in the longitudinal direction of the polyolefin resin film of the present invention at 120°C is 9%. If it is 9% or less, the tear strength is small, and at the same time, the shrinkage during heat sealing or retort of the package is small, and the appearance of the package is excellent. It is preferably 8%, more preferably 7%, more preferably 6%, even more preferably 5%, and particularly preferably 4%. The lower limit of the longitudinal heat shrinkage rate of the polyolefin resin film of the present invention is 1%. If it is 1% or more, the tear strength tends to be low. It is preferably 2%.
[0061] To achieve straight cutability, the lower limit of the longitudinal orientation coefficient ΔNx must be 0.0150, but if the upper limit of the longitudinal thermal shrinkage rate at 120°C is 9%, whiskers are less likely to occur. The reason for this is that when the film is thermally melted by heat sealing, orientation is less likely to remain in the sealed area or at the sealed edge, so the film laminated to the base film is restrained by the base film during heat sealing and is less likely to shrink. This is thought to be because force is applied to the film, making it difficult to re-orient the film. The upper limit of the heat shrinkage rate of the polyolefin resin film of the present invention in the direction perpendicular to the longitudinal direction (width direction) is preferably 1%. If it is 1% or less, the tear strength in the longitudinal direction is likely to be small, and straight cuttability is likely to be obtained. It is preferably 0.5%. The lower limit of the heat shrinkage rate of the polyolefin resin film of the present invention in the direction perpendicular to the one direction is -5%. If it is -5% or more, elongation occurs when heat sealing is performed, and the appearance of the package may be deteriorated. It is preferably -2%.
[0062] (Hayes) Haze was measured according to JIS K7136. Measurements were made on the polyolefin resin film before lamination (N=3), and the average value was calculated. The upper limit of the haze is preferably 80%, more preferably 70%, even more preferably 60%, and even more preferably 50%. When it is 80% or less, the visibility of the contents is excellent. The lower limit of the haze is preferably 20%.
[0063] (tear strength) The upper limit of the longitudinal tear strength of the polyolefin resin film of the present invention is preferably 0.30 N. If this limit is exceeded, the laminate film may become difficult to tear. The upper limit is more preferably 0.16 N. The lower limit of the longitudinal tear strength of the polyolefin resin film of the present invention is preferably 0.02 N. If it is smaller than this, the resistance to bag rupture may deteriorate. It is more preferably 0.03 N.
[0064] (Puncture strength) The lower limit of the puncture strength of the polyolefin resin film of the present invention is preferably 10 N, more preferably 15 N / μm, even more preferably 18 N, and even more preferably 20 N. If it is 15 N or more, pinholes are unlikely to occur when a protrusion hits a package. The upper limit of the puncture strength is preferably 35 N. If it is 35 N or less, the stiffness is not too strong, and handling becomes easy when it is made into a film or laminate.
[0065] (Puncture strength) The lower limit of the puncture strength per μm of the polyolefin resin film of the present invention is preferably 0.13 N / μm, more preferably 0.15 N / μm. If it is less than the above, pinholes may occur when the protrusion hits the package. The upper limit of the puncture strength is preferably 0.40 N / μm. If it exceeds the above, the film may feel too stiff, and handling may be difficult when it is made into a film or laminate.
[0066] (Wetting tension) The lower limit of the wet tension of the surface of the polyolefin resin film of the present invention to be laminated with at least one film selected from the group consisting of polyamide resin film, polyester resin film, and polypropylene resin film is preferably 30 mN / m, more preferably 35 mN / m. If it is less than the above, the laminate strength may decrease. The upper limit of the wet tension is preferably 55 mN / m, more preferably 50 mN / m. If it exceeds the above, blocking of the roll of the polyolefin resin film may occur.
[0067] (Structure of laminate and manufacturing method) The laminate using the polyolefin resin film of the present invention is a laminate using the polyolefin resin film as a sealant and at least one film selected from the group consisting of polyamide resin film, polyester resin film, and polypropylene resin film. In addition, as a known technique, a substrate film that has been coated or vapor-deposited for the purpose of imparting adhesiveness or barrier properties may be used, or aluminum foil may be further laminated. Specific examples include biaxially oriented PET film / aluminum foil / sealant, biaxially oriented PET film / biaxially oriented nylon film / sealant, biaxially oriented nylon film / sealant, biaxially oriented polypropylene film / sealant, biaxially oriented PET film / biaxially oriented nylon film / aluminum foil / sealant, etc. Among these, when a sealant with a small longitudinal orientation is used for the biaxially oriented nylon film, the straight cut property of the laminate is greatly deteriorated. By using the polyolefin resin film of the present invention as a sealant, a laminate with good straight cut property can be produced in any configuration. The lamination may be performed by a known method such as dry lamination or extrusion lamination, but any lamination method can be used to produce a laminate having good straight cutability.
[0068] (Laminate properties) (tear strength) The upper limit of the longitudinal tear strength of the laminate of the present invention is preferably 0.50 N. If it is 0.50 N or less, the laminate is easily torn. It is more preferably 0.40 N, even more preferably 0.35 N, and even more preferably 0.30 N. The lower limit of the longitudinal tear strength may be 0.05 N.
[0069] (Straight cutting ability) The straight cuttability refers to the ability of a film or laminate to be torn straight in one direction when torn. Measurement was performed as follows. In this example, the film was stretched in the longitudinal direction, so the heat shrinkage rate was high in the longitudinal direction, and the one direction was the longitudinal direction. Therefore, the straight cutting ability was evaluated only in the longitudinal direction. The film or laminate film was cut into a strip measuring 150 mm in the longitudinal direction and 60 mm perpendicular to the longitudinal direction, and a 30 mm cut was made in the longitudinal direction from the center of the short side. The sample was torn in accordance with JIS K7128-1:1998. When the sample had been torn 120 mm in the longitudinal direction, not including the 30 mm cut, the distance traveled in the longitudinal and perpendicular directions was measured and the absolute value was recorded. Measurements were made with N=3 for both the case where the right-hand piece was clamped in the upper grip and the case where the left-hand piece was clamped in the upper grip, and the average value for each was calculated. The larger value of the measurement results for the right and left sides was used.
[0070] (Straight cutting ability) The upper limit of the straight cuttability of the laminate of the present invention is preferably 8 mm, more preferably 5 mm, and further preferably 3 mm. If it is 8 mm or less, the package is unlikely to come apart. The lower limit may be 0.5 mm.
[0071] (Tearful farewell) The upper limit of tearing of the laminate of the present invention is not particularly limited, but is preferably 15 mm, more preferably 10 mm, even more preferably 6 mm, and particularly preferably 5 mm. If it is 15 mm or less, the contents are unlikely to spill when the package is torn. The lower limit may be 1 mm.
[0072] (beard incidence) The laminate film of the polyolefin resin film and the base film of the invention was heat-sealed with the heat-seal film layers facing each other to create a four-sided sealed bag with inner dimensions of 120 mm in the longitudinal direction and 170 mm in the longitudinal and perpendicular directions. A notch was made at the end of the four-sided sealed bag, which was then torn by hand in the longitudinal direction. The whisker occurrence rate calculated from the number of times thread-like film pieces (whiskers) occurred and the number of times it was torn is preferably 30% or less, more preferably 25% or less, even more preferably 20% or less, particularly preferably 16% or less, and most preferably 10% or less. The laminate film was prepared by mixing the polyolefin resin film of the present invention and a base film (Toyobo biaxially oriented nylon film, N1102, thickness 15 μm, orientation angle 22° to the longitudinal direction) with 33.6 parts by weight of an ester-based dry lamination adhesive (Toyo Morton, TM569), 4.0 parts by weight of a hardener (Toyo Morton, CAT10L), and 62.4 parts by weight of ethyl acetate, with an adhesive coating amount of 3.0 g / m. 2 The laminated film was kept at 40° C. and aged for 3 days to obtain a laminated film. Hair growth rate = Hair growth count / Tear count x 100(%)
[0073] (Finished bag) The polyolefin resin film sides of the laminate films were overlapped and heat sealed at 0.2 MPa for 1 second with a seal bar width of 10 mm and a heat seal temperature of 220° C. to create a four-sided sealed bag with inner dimensions of 120 mm in the MD direction and 170 mm in the TD direction. When the finished state of this four-sided sealed bag was visually confirmed, it was preferable that there was no deformation near the heat sealed parts, and furthermore that the bag was a perfect rectangle.
[0074] (Retort shrinkage rate) The upper limit of the retort shrinkage of the laminate of the present invention is preferably 5%. If it exceeds this limit, the appearance of the package after retort may deteriorate. More preferably, it is 4%. The lower limit of the retort shrinkage in one direction is -5%. If it is less than this limit, the elongation after retort may be large, which may cause the bag to break. More preferably, it is -2%, and even more preferably, it is 0%.
[0075] (Heat seal strength) The lower limit of the heat seal strength of the laminate of the present invention before retort is preferably 35N / 15mm, more preferably 40N / 15mm. If it is less than the above, the bag rupture resistance may deteriorate. It is preferable that the heat seal strength maintains 35N / 15mm or more even after retort treatment at 121°C for 30 minutes. The upper limit of the heat seal strength is preferably 60N / 15mm. In order to exceed the above range, it is necessary to increase the thickness of the film, which may result in higher costs.
[0076] (Heat seal start temperature) The lower limit of the heat seal initiation temperature of the laminate of the present invention before retort is preferably 190°C or less, more preferably 185°C or less, and even more preferably 180°C or less. If it exceeds 190°C, the shrinkage of the film during bag making will be large, impairing the appearance, and the bag making speed will decrease, resulting in high costs. The lower limit of the heat seal temperature is preferably 150°C or more, and even more preferably 160°C or more. If it is less than the above, the heat of the retort treatment may cause the inner surface of the film to fuse.
[0077] (packaging) The laminate is arranged to enclose the contents, such as foodstuffs, in order to protect the contents from dust, gases, etc. in the natural world, and is called a package. The package is produced by cutting out the laminate, bonding the inner surfaces together with a heated heat seal bar or ultrasonic waves, etc., and forming it into a bag shape. For example, a four-sided sealed bag in which two rectangular laminates are stacked with the sealant side facing inward and the four sides are heat sealed is widely used. The contents may be foodstuffs, but may also be other products such as daily necessities, and the shape of the package may be a shape other than a rectangle, such as a standing pouch or a pillow package. A package that can withstand the heat of thermal sterilization using hot water whose boiling point has been raised to 100°C or higher by pressurization or other methods is called a retort package, and a film intended to provide such a package is called a retort film.
[0078] (Bag resistance) A four-side sealed bag made from the laminate of the present invention is dropped and repeatedly dropped until the bag breaks. The number of repeated drops is measured. From a practical standpoint, it is preferable that the number of drops at which the proportion of bags remaining unbroken is 5 or more, more preferably 10 or more, even more preferably 11 or more, and even more preferably 12 or more. EXAMPLES
[0079] The present invention will be described in detail below with reference to examples, but is not limited thereto. The properties obtained in each example were measured and evaluated by the following methods. In the evaluation, the longitudinal direction of the film was defined as the MD direction, and the direction perpendicular to the longitudinal direction (width direction) was defined as the TD direction.
[0080] (1) Resin density The density was evaluated according to JIS K7112:1999 D method (density gradient tube). N=3 measurements were made and the average value was calculated.
[0081] (2) Melt flow rate (MFR) Measurements were performed at 230°C and a load of 2.16 kg based on JIS K-7210-1. N=3 measurements were performed, and the average value was calculated.
[0082] (3) Heat shrinkage rate The film before lamination was cut into 120 mm squares. Marked lines were drawn at 100 mm intervals in both the MD and TD directions. The sample was hung in an oven kept at 120°C and heat-treated for 30 minutes. The distance between the marked lines was measured, and the thermal shrinkage rate was calculated according to the following formula. Measurements were made with N=3, and the average value was calculated. Heat shrinkage rate = (gauge length before heat treatment - gauge length after heat treatment) / gauge length before heat treatment x 100 (%)
[0083] (4) Tear strength The tear strength was measured according to JIS K7128-1: 1998. Evaluation was carried out on the base film before lamination and on the laminate film. Measurements were made in the MD direction and TD direction with N=3 each, and the average value was calculated.
[0084] (5) Longitudinal orientation factor The refractive index was evaluated according to JIS K 0062:1999 method for measuring the refractive index of chemical products. Measurements were performed with N=3, and the average value was calculated. The longitudinal orientation coefficient ΔNx was calculated using Equation 1. ΔNx=Nx-(Ny+Nz) / 2 (Equation 1) Nx: Refractive index in the longitudinal direction Ny: Refractive index in the longitudinal direction and perpendicular direction to the thickness direction Nz: Refractive index in the thickness direction
[0085] (6) Straight cutting ability The straight cut property indicates the ability to tear a laminate film (laminate) straight in one direction when it is torn. The measurement was performed by the following method. In this example, the film was stretched in the MD direction, so the heat shrinkage rate was high in the MD direction, and the one direction was the MD direction. Therefore, the straight cut property was evaluated only in the MD direction. The laminate film was cut into strips measuring 150 mm in the MD direction and 60 mm in the TD direction, and a 30 mm cut was made in the center of the short side along the MD direction. The sample was torn in accordance with JIS K7128-1:1998. When the sample was torn 120 mm in the MD direction, not including the 30 mm cut, the distance traveled in the TD direction was measured and the absolute value was recorded. Measurements were performed with N=3 for both the case where the right-hand piece was clamped in the upper grip and the case where the left-hand piece was clamped in the upper grip, and the average value for each was calculated. The larger value of the measurement results for the right and left sides was used.
[0086] (7) Tearful Parting The laminated films were placed face to face with the heat seal film and heat sealed to create a four-sided sealed bag with inner dimensions of 120mm in the MD and 170mm in the TD. A notch was made at the edge of the four-sided sealed bag and it was torn in the MD by hand. The cut was continued to the opposite end and the deviation of the tear lines of the film on the front and back of the bag was measured. The average value was calculated for both the right-hand side facing direction and the left-hand side facing direction, with N=3 for each, and the larger measurement value was used.
[0087] (8) Retort shrinkage rate The laminate film was cut into 120 mm squares. Marked lines were drawn at 100 mm intervals in both the MD and TD directions. The film was retorted in hot water at 121°C for 30 minutes. The distance between the marked lines was measured, and the retort shrinkage rate was calculated according to the following formula. Measurements were performed with N=3 for each film, and the average value was calculated. Retort shrinkage rate = (gauge length before treatment - gauge length after treatment) / gauge length before treatment x 100 (%)
[0088] (9) Heat seal strength The heat sealing conditions and strength measurement conditions are as follows. That is, the polyolefin resin film sides of the laminate films obtained in the examples and comparative examples were overlapped with each other, and heat sealed at a pressure of 0.2 MPa for 1 second with a seal bar width of 10 mm and a heat seal temperature of 220°C, and then allowed to cool. Next, retort treatment was performed with hot water at 121°C for 30 minutes. Test pieces of 80 mm in the MD direction and 15 mm in the TD direction were cut from the films heat sealed at each temperature, and the peel strength was measured when the heat sealed part was peeled off at a crosshead speed of 200 mm / min for each test piece. The test machine used was a universal material testing machine 5965 manufactured by Instron Instruments. Measurements were performed N=3 times for each, and the average value was calculated.
[0089] (10) Sealing start temperature The seal start temperature is an item related to productivity when assuming continuous production with a bag making machine. Good bag making suitability means that sufficient sealing can be obtained within a temperature range where the base film does not shrink or break. The heat seal temperature was evaluated as follows. In the measurement of the heat seal strength, the temperature of the heat seal bar was changed in 5°C increments, and the heat seal strength was measured for each case with N = 3. The heat seal strength was calculated as a weighted average of the heat seal temperature just before the heat seal strength exceeded 30 N and the heat seal temperature just after it exceeded that temperature.
[0090] (11) Incidence of facial hair The laminated films were placed face to face with the heat seal film and heat sealed to create a four-sided sealed bag with inner dimensions of 120mm in the MD direction and 170mm in the TD direction. A notch was made at the edge of the four-sided sealed bag, and it was torn by hand in the MD direction. The occurrence rate was calculated from the number of times that thread-like film pieces (whiskers) occurred. This was done with n=100 in both the right-hand side facing direction and the left-hand side facing direction, and the larger measurement value was used. Hair growth rate = Hair growth count / Tear count x 100(%)
[0091] (12) Finished bag making The polyolefin resin film sides of the laminate films were overlapped and heat sealed at 0.2 MPa for 1 second with a seal bar width of 10 mm and a heat seal temperature of 220°C to create a four-sided sealed bag with inner dimensions of 120 mm in the MD direction and 170 mm in the TD direction. The finished state of this four-sided sealed bag was visually inspected. ○: There is no deformation near the heat seal area, and the bag is completely rectangular. △: Little deformation near the heat seal area ×: Large deformation near the heat-sealed portion, and the edges of the bag are wavy
[0092] (13) Bag breakage resistance The laminate film was cut out to prepare a four-sided sealed bag with an inner dimension of 170 mm length and 120 mm width, which contained 300 ml of saturated saline. The heat sealing conditions were 0.2 MPa pressure for 1 second, a seal bar width of 10 mm, and a heat sealing temperature of 220°C. After the bag making process, the ends of the four-sided sealed bag were cut off to a seal width of 5 mm. The four-sided sealed bag was retorted at 121°C for 30 minutes. It was then left in a -5°C environment for 8 hours, and in that environment, the four-sided sealed bag was dropped from a height of 1.0 m onto a flat concrete floor. The bag was repeatedly dropped until it broke, and the number of repeated drops was measured and the following stages were set. The number of bags was 20 for each level. ◎: 13 or more drops that result in a 50% survival rate ○: The number of drops required to reach a survival rate of 50% is between 10 and 12 △: The number of drops required to reach 50% survival is between 5 and 9 ×: The number of drops that results in a survival rate of 50% is 4 or less
[0093] (14) Orientation angle The orientation angle (°) of the base film was measured using a molecular orientation meter MOA-6004 manufactured by Oji Scientific Instruments Co., Ltd. A sample was cut out to 120 mm in the MD direction and 100 mm in the TD direction, and placed on the measuring instrument. The measured Angle value was taken as the orientation angle. The MD direction is 0°. Measurements were made with N=3, and the average value was calculated.
[0094] (15)Puncture strength The puncture strength of the film before lamination and the laminate was measured at 23°C in accordance with "2. Strength Test Method" in "Standards for Foods, Additives, etc., Part 3: Apparatus and Containers and Packaging" (Ministry of Health and Welfare Notification No. 20, 1982) in the Food Sanitation Act. A needle with a tip diameter of 0.7 mm was pierced into the film at a puncture speed of 50 mm / min, and the strength at which the needle penetrated the film was measured. The measured value was divided by the film thickness to calculate the puncture strength [N / μm] per 1 μm of film. N=3 measurements were made and the average value was calculated.
[0095] Example 1 (Polyolefin resin film) (Raw materials used) For the polypropylene-based resin films of Examples 1 to 7 and Comparative Examples 1 to 10, raw materials were prepared based on the resin compositions and ratios of each layer shown in Tables 1 and 2 below. These raw materials were mixed uniformly to obtain a mixed raw material for producing a polyolefin-based resin film. 1) Raw material A: Sumitomo Chemical's propylene-ethylene block copolymer WFS5293-22 (ethylene content 7% by weight, resin density 891 kg / m3, MFR 3.0 g / 10 min at 230°C and 2.16 kg, melting point 164°C) 2) Raw material B: Ethylene-propylene copolymer elastomer Toughmer P0480 manufactured by Mitsui Chemicals (propylene content 27% by weight, resin density 870 kg / m3, MFR 1.8 g / 10 min at 230°C and 2.16 kg, melting point 48°C) 3) Raw material C: Sumitomo Chemical's propylene-ethylene random copolymer S131 (ethylene content 5.5% by weight, resin density 890 kg / m3, MFR 1.5 g / 10 min at 230°C and 2.16 kg, melting point 132°C, Ziegler-Natta catalyst) 29 4) Raw material D: Propylene-ethylene random copolymer WFW4M manufactured by Japan Polypropylene (ethylene content 7% by weight, resin density 900 kg / m3, MFR 7.0 g / 10 min at 230°C and 2.16 kg, melting point 136°C, metallocene catalyst) 5) Raw material E: Propylene-ethylene random copolymer WFX4M manufactured by Japan Polypropylene (ethylene content 7% by weight, resin density 900 kg / m3, MFR 7.0 g / 10 min at 230°C and 2.16 kg, melting point 125°C, metallocene catalyst)
[0096] (Melt Extrusion) The mixed raw materials for the intermediate layer were extruded in a three-stage single-screw extruder with a screw diameter of 90 mm, and the mixed raw materials for the laminate layer and heat seal layer were extruded in three-stage single-screw extruders with diameters of 45 mm and 65 mm, respectively, in the order of laminate layer / intermediate layer / heat seal layer. The preland was made into two stages with a width of 800 mm, and the step part was curved to ensure uniform flow of the molten resin. The extrusion was performed at an outlet temperature of 230° C. The thickness ratios of the laminate layer / intermediate layer / heat seal layer were 25% / 50% / 25%, respectively. (cooling) The molten resin sheet emerging from the die was cooled with a cooling roll at 21°C to obtain an unstretched polyolefin resin film with a layer thickness of 210 (μm). When cooling with the cooling roll, both ends of the film on the cooling roll were fixed with air nozzles, and the entire width of the molten resin sheet was pressed against the cooling roll with an air knife, and at the same time, a vacuum chamber was operated to prevent air from being drawn in between the molten resin sheet and the cooling roll. The air nozzles were installed in series on both ends in the direction of film travel. The die was surrounded by a sheet to prevent the molten resin sheet from being exposed to wind.
[0097] (preheat) The unstretched sheet was preheated by leading it to a group of heated rolls and bringing the sheet into contact with the rolls. The temperature of the preheating rolls was 105° C. Multiple rolls were used to preheat both sides of the film. (longitudinal stretching) The unstretched sheet was introduced into a longitudinal stretching machine and stretched 3.5 times by the roll speed difference to a thickness of 60 μm. The temperature of the stretching rolls was 105° C. (Annealing treatment) The film was heat-treated at 130° C. using an annealing roll. Both sides of the film were heat-treated using multiple rolls. (relaxation process) The speed of the roll placed next to the annealing roll was reduced by 5% as a relaxation rate relative to the annealing roll to relax the film.
[0098] (Corona treatment) One side of the film (the lamination side) was subjected to a corona treatment. (winding) The film was formed at a winding roll speed of 20 m / min. The edge portions of the formed film were trimmed and the film was wound in a roll. The thickness of the obtained film was 60 μm.
[0099] (Creating laminate film) The polyolefin resin film obtained in Example 1 and a base film (Toyobo biaxially oriented nylon film, N1102, thickness 15 μm, orientation angle 22° to MD direction) were laminated with an ester-based adhesive obtained by mixing 33.6 parts by weight of an ester-based dry lamination adhesive (Toyo Morton, TM569), 4.0 parts by weight of a hardener (Toyo Morton, CAT10L), and 62.4 parts by weight of ethyl acetate, at a coating amount of 3.0 g / m 2 The laminated film was kept at 40° C. and aged for 3 days to obtain a laminated film.
[0100] Example 2 In Example 1, the raw materials shown in Table 1 were used, and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the thickness of the unstretched polyolefin resin film was 228 μm, the longitudinal stretching ratio was 3.8 times, and the relaxation rate in the relaxation step was 7%. A laminate was obtained in the same manner as in Example 1.
[0101] Example 3 A 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the raw materials shown in Table 1 were used and the relaxation rate in the relaxation step was 7%. A laminate was obtained in the same manner as in Example 1.
[0102] Example 4 In Example 1, the raw materials shown in Table 1 were used, and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the thickness of the unstretched polyolefin resin film was 228 μm and the longitudinal stretching ratio was 3.8 times. A laminate was obtained in the same manner as in Example 1.
[0103] Example 5 A 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the raw materials shown in Table 1 were used and the relaxation rate in the relaxation step was 6%. A laminate was obtained in the same manner as in Example 1.
[0104] Example 6 In Example 1, the raw materials shown in Table 1 were used, and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the thickness of the unstretched polyolefin resin film was 228 μm and the longitudinal stretching ratio was 3.8 times. A laminate was obtained in the same manner as in Example 1.
[0105] Example 7 In Example 1, the raw materials shown in Table 1 were used, and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the thickness of the unstretched polyolefin resin film was 186 μm and the longitudinal stretching ratio was 3.1 times. A laminate was obtained in the same manner as in Example 1.
[0106] (Comparative Example 1 and Comparative Example 2) In Example 1, the raw materials shown in Table 2 were used, the thickness of the unstretched polyolefin resin film was 60 μm, and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the longitudinal stretching, annealing treatment, and relaxation steps were not performed. A laminate was obtained in the same manner as in Example 1.
[0107] Comparative Example 3 In Example 1, the raw materials shown in Table 2 were used, the thickness of the unstretched polyolefin resin film was 240 μm, the longitudinal stretching ratio was 4.0 times, and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that no relaxation step was performed. A laminate was obtained in the same manner as in Example 1.
[0108] Comparative Example 4 In Example 1, the raw materials shown in Table 2 were used, the thickness of the unstretched polyolefin resin film was 270 μm, the longitudinal stretching ratio was 4.5, the annealing temperature was 120° C., and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that no relaxation step was performed.
[0109] Comparative Example 5 In Example 1, the raw materials shown in Table 2 were used, the thickness of the unstretched polyolefin resin film was 120 μm, the longitudinal stretching ratio was 2.0 times, the annealing temperature was 120° C., and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that no relaxation step was performed.
[0110] Comparative Example 6 In Example 1, the raw materials shown in Table 2 were used, the thickness of the unstretched polyolefin resin film was 186 μm, the longitudinal stretching ratio was 3.1 times, the annealing temperature was 120° C., and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that no relaxation step was performed.
[0111] Comparative Example 7 A polyolefin resin film having a thickness of 60 μm was obtained in the same manner as in Example 1, except that the relaxation step was not performed.
[0112] Comparative Example 8 A polyolefin resin film having a thickness of 60 μm was obtained in the same manner as in Example 1, except that the annealing step and the relaxation step after stretching were not performed.
[0113] Comparative Example 9 In Example 1, the raw materials shown in Table 2 were used, and a 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the thickness of the unstretched polyolefin resin film was 150 μm and the longitudinal stretching ratio was 2.5 times. A laminate was obtained in the same manner as in Example 1.
[0114] Comparative Example 10 A 60 μm polyolefin resin film was obtained in the same manner as in Example 1, except that the raw materials shown in Table 2 were used, the thickness of the unstretched polyolefin resin film was 300 μm, and the stretching ratio was 5.0 times. A laminate was obtained in the same manner as in Example 1.
[0115] In Comparative Examples 1 and 2, the films were unstretched and therefore had poor straight cutability. In Comparative Example 3, the stretch ratio was high and the x-axis orientation coefficient of the film was large, so whiskers were easily generated when the film was opened. In addition, the film had poor thermal dimensional stability because there was no relaxation after annealing. In Comparative Example 4, at least the heat seal layer did not contain an ethylene-propylene random copolymer, and the stretch ratio was high, so that the low-temperature sealability was poor. In Comparative Example 5, the stretching ratio was low and the x-axis orientation coefficient of the film was small, so that the straight cuttability was poor. In Comparative Examples 6 to 8, there was no relaxation after annealing, and therefore the thermal dimensional stability was poor. In Comparative Example 9, the x-axis orientation coefficient was small, and therefore the straight cut property was poor. In Comparative Example 10, since the x-axis orientation coefficient was large, whiskers were likely to occur when the package was opened. The above results are shown in Tables 1 and 2.
[0116] [Table 1]
[0117] [Table 2]
[0118] In Tables 1 and 2, the evaluation results marked as "Not measurable*" indicate that the film was torn in the MD during the property evaluation, and no measurement value could be obtained. [Industrial Applicability]
[0119] INDUSTRIAL APPLICABILITY The present invention makes a great contribution to industry by providing a retort pouch which can be opened straight with only slight creases in the opening direction and which is less likely to produce whiskers when opened.
Claims
1. A polyolefin-based resin film made of a polypropylene-based resin composition, comprising 40 to 97 parts by weight of a propylene-ethylene block copolymer consisting of a polymer portion mainly composed of propylene and a copolymer portion of propylene and ethylene having an ethylene content of 20 to 50 parts by weight, 0 to 50 parts by weight of a propylene-α-olefin random copolymer or a propylene homopolymer, and 3 to 10 parts by weight of at least one elastomer selected from the group consisting of an ethylene-propylene copolymer elastomer, a propylene-butene copolymer elastomer, and an ethylene-butene copolymer elastomer, the polyolefin-based resin film having a thermal shrinkage rate in the longitudinal direction of 1% or more and 9% or less, and an x-axis orientation coefficient ΔNx calculated from a refractive index of 0.0180 or more and 0.0220 or less.
2. The polyolefin resin film according to claim 1 , which has a multi-layer structure of at least two layers.
3. A laminate comprising at least one substrate film selected from the group consisting of the polyolefin resin film according to claim 1, a polyamide resin film, a polyester resin film, and a polypropylene resin film.
4. The laminate according to claim 3, having a straight cut ability of 5 mm or less.
5. A package comprising the laminate according to claim 4.
6. The packaging body according to claim 5, which is for retort use.
Citation Information
Patent Citations
Heat-sealable, uniaxially oriented propylene film with tear directionality
JP2012500307A
Packaging material for retort food
JP2014141302A
Heat-sealable, uniaxially oriented propylene film with directional tear resistance.
JP2015527943A
Sealant film and packaging material
WO2017098953A1
Polyolefin resin film
WO2019123944A1
Cited By
Oxygen-absorbing sealant film
WO2026204993A1